2000
DOI: 10.1063/1.480621
|View full text |Cite
|
Sign up to set email alerts
|

Elementary mechanisms governing the dynamics of silica

Abstract: A full understanding of glasses requires an accurate atomistic picture of the complex activated processes that constitute the low-temperature dynamics of these materials. To this end, we generate over five thousand activated events in a model silica glass, using the activation-relaxation technique; these atomistic mechanisms are analyzed and classified according to their activation energies, their topological properties and their spatial extent. We find that these are collective processes, involving ten to hun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In terms of stage I, a low energy barrier usually results from annihilation/creation of one or two pairs of dangling bonds. 26 This is quite possible in MCM-41 due to the amorphous nature of the silica phase and the existence of surface dangling bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of stage I, a low energy barrier usually results from annihilation/creation of one or two pairs of dangling bonds. 26 This is quite possible in MCM-41 due to the amorphous nature of the silica phase and the existence of surface dangling bonds.…”
Section: Resultsmentioning
confidence: 99%
“…As the kinetically related pore closure process happens mainly during heating, the activation energy needed for atoms to transfer from matrix to porous region must be higher than in the hold stage (at least below 2415 K) for a pure diffusion process. Previous studies 26 concluded that diffusion in the silica phase is a collective process that can involve different number of atoms leading to a continuous range of activation energies. The diffusion of the pore interface may involve almost all atoms, as the surface boundaries simultaneously move toward the porous region, thus requiring a higher activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…15 This has also been identified as an important relaxation mechanism in a-SiO 2 , and it appears to be characteristic of chemically-ordered networks. 47 The latter point being an assumption of our model, it is expected that these mechanisms also play an important role during bombardment-induced densification. More precisely, since coordination numbers do not show systematic variations with increasing density, bond-switching is expected to dominate over the annihilation of coordination defects.…”
Section: B Structure Of Samples Grown With Bombardmentmentioning
confidence: 99%
“…47 The substrate is first subjected to an extensive thermal annealing cycle in order to allow the surface to relax. A 3Å-thick layer at the bottom is held fixed, in order to mimic a semi-infinite system, but also to prevent the substrate from moving because of momentum transfer from incoming atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…(3) The configuration is then pushed slightly further, away from this saddle point, and its energy is minimized using a standard minimization technique. ART and similar methods have been applied with success to study the topology of the energy landscape and activated mechanisms in a wide range of materials including amorphous and crystalline semiconductors [14,15,16], glassy materials [17], atomic clusters [9,18], and proteins [19,20,21,22,23]. A recent study has shown that ART compares favorably with other related techniques in terms of efficiency and completeness of finding activated mechanisms [11].…”
Section: Sampling the Energy Landscape Using Activated Methodsmentioning
confidence: 99%